IMPLEMENTASI METODE AL-QOSIMI DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR'AN SISWA KELAS XI MADRASAH ALIYAH AL-ISLAM JAMSAREN SURAKARTA TAHUN PELAJARAN 2023/2024 - Sholihah, Ervin Jamilatus; Khoir, Mulyanto Abdullah; Rochmawan, Alfian Eko (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
The objectives of this study is to determine the quality of Qur'an memorization of class XI students at Madrasah Aliyah Al-Islam Jamsaren Surakarta and to determine the implementation of the Al-Qosimi method in learning tahfidzul qur'an at Madrasah Aliyah Al-Islam Jamsaren Surakarta. This research used qualitative method and descriptive approach. This research was conducted at Madrasah Aliyah Al-Islam Jamsaren Surakarta in September - December 2023. Data collection was conducted by interviews, observation, and documentation. Data analysis used data collection analysis techniques, data reduction, data presentation, conclusion drawing or verification. To test the validity of the data was done through Credibility Test. The results show that, the quality of memorization of the Qur'an of class XI students at Madrasah Aliyah Al-Islam Jamsaren Surakarta can be said to be still uneven, this is due to differences in the ability to memorize from each student and lack of motivation from students. As for the implementation of the Al-Qosimi method in learning tahfidzul qur'an at Madrasah Aliyah Al-Islam Jamsaren is quite good, this can be seen from the results of researchers' observations in teaching and learning activities for tahfidzul qur'an subjects that are in accordance with the guidelines or technical instructions in the implementation of the Al-Qosimi method, namely by having muroja'ah together first then reading 40 times before starting to memorize new memorization, and memorization deposits by listening to friends first before depositing memorization to the respective halaqoh teacher.